Analysis of Selected Pavement Serviceability Parameters - Celko, Jan; Kovac, Matus; Decky, Martin (Communications - Scientific letters of the University of Zilina, 2011)
The parameters of pavement serviceability have the notable effect to the road life time and to the conditions of safe and comfortable driving. The serviceability of flexible pavements is defined by three parameters: skid resistance, unevenness and pavement distress. The Slovak Road Administration observes 24 specific road sections on which the parameters have been measured two times per year since 1998. The obtained data should be used for determination of the degradation models that describe the qualitative decreasing of the parameters depending on time and traffic load. The functions are very important for definition of the optimal road maintenance and rehabilitation. The degradation models describing the parameters changes over time are the substantial research problem in dependence on many affecting factors. The results of pavement serviceability parameters evaluation are presented in the paper. The basic functions are described and discussed.